KERJASAMA MILITER RUSIA – CINA DI KAWASAN ASIA TIMUR TAHUN 2012 – 2016 - Patricia Hapsari (Jurusan Ilmu Hubungan Internasional, 2016)
This paper ponders the recent military co-operation between Russia and China in East Asia. Following the US’s pivot to Asia, Putin also began to eyed Asia through ‘looking east policy. It commenced with restoring bilateral relationship with its east neighbouring countries mainly, China. To some extent the military cooperation between Russia and China have been based on the same perspective and mutual interest related to the growing presence of the US in East Asia. Using external balancing perspective, this paper argues that the military cooperation between Russia and China have been driven by external balancing strategies towards the augmentation of US maritime force in East Asia. It is conducted through mainly through transfer of weaponry and military training.